2004
DOI: 10.1590/s0041-87812004000200003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the morphologic alterations of vocal cords from adult autopsies and the cause of death

Abstract: PURPOSE:The purpose of this study was to identify the possible alteration in the thickness of the epithelium basal membrane of the vocal cords and correlate it with the cause of death.METHOD: Larynxes collected from adult autopsies during the period of 1993 to 2001 were utilized. We used the hematoxylin-eosin and periodic acid-Schiff staining methods for the morphological and morphometric analysis.RESULTS: Sixty-six vocal cords were analysed; increased thickness was identified in 14 cases (21.2%), with equal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Later, the larynx was sectioned transversally at points above and below the glottic cavity and within 3cm one from the other. Parallel sections to the extremity of the vocal folds were made, transversally, and the fragment was processed for paraffin preparation 4 . We performed hematoxylineosin staining (HE) for morphological analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, the larynx was sectioned transversally at points above and below the glottic cavity and within 3cm one from the other. Parallel sections to the extremity of the vocal folds were made, transversally, and the fragment was processed for paraffin preparation 4 . We performed hematoxylineosin staining (HE) for morphological analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the importance of VF in protecting the body against infectious agents has been recently discussed 1,2 . In studies conducted with true vocal folds we can find the description of lesions such as thickness of basal membrane of true vocal folds epithelium and their relation with infectious diseases 4 , but there is no report on vestibular folds. As to microscopic lesions of VF, there are reports of lymphoid follicle hyperplasia of VF and the suggestion of the term laryngeal tonsil 5 to name the structure, since it has been observed that this tissue presents an organization and that it could be replaced by larynx associated lymphoid tissue 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Later, the larynx was sectioned transversally at points above and below the glottic cavity and within 3cm one from the other. Parallel sections to the extremity of the vocal folds were made, transversally, and the fragment was processed for paraffin preparation 4 . We performed hematoxylin-eosin staining (HE) for morphological analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the importance of VF in protecting the body against infectious agents has been recently discussed 1 , 2 . In studies conducted with true vocal folds we can find the description of lesions such as thickness of basal membrane of true vocal folds epithelium and their relation with infectious diseases 4 , but there is no report on vestibular folds. As to microscopic lesions of VF, there are reports of lymphoid follicle hyperplasia of VF and the suggestion of the term laryngeal tonsil 5 to name the structure, since it has been observed that this tissue presents an organization and that it could be replaced by larynx associated lymphoid tissue 2 .…”
Section: Introductionmentioning
confidence: 99%